Compact Ultra-wide-band Bandpass Filter using Square Complimentary Split Ring Resonator - Singh, Inder P.; Bhatt, Praveen (Recent Advances in Electrical & Electronic Engineering, 2020)
Background: In this paper, an ultra-wide-band bandpass filter with large stopband using interdigital coupled lines and pair of Square Complimentary Split Ring Resonator (SCSRR) is proposed. Methods: Interdigital coupled lines give bandpass characteristics and pair of SCSRR provides tuning of cut off frequencies and transmission zeroes on both side of the passband. In the passband, two transmission poles are achieved. The tightly coupled structure provides a wide stopband and sharp skirt response. Results: Dielectric constant 2.6 and its thickness of 0.787 mm is used to implement the design. Centre frequency of the proposed design is 5.1 GHz. Bandwidth at -3 dB is 3.5 GHz to 6.5 GHz. Conclusion: The proposed structure is simulated in Ansoft HFSS.
Keywords: split-ring